The Transformational Leadership of Academic Club Moderators in the Basic Education Department - Valera, Riza B. (International Journal of Research in Interdisciplinary Studies, 2023)
This study is motivated by several reasons, including the findings of accreditation in the Basic Education Department. The department's objective goes beyond attaining a partially implemented rating. Recognizing this gap, an accrediting body has underscored the im-portance of aligning short-term plans with the dynamic pulse of our evolving society. Consequently, there is a pressing need for a well-defined leadership program for the club moderators, ensuring its integration into the organization's annual operational plan. Transformational leadership is a leadership style that has been proven to have a positive effect on organizational outcomes. Academic clubs are organizations formed and approved by the institution for students who share a common interest in a particular academic field This research comprehensively examines transformational leadership demonstrated by academic club moderators within the Basic Education Department. It scrutinizes the transformative attributes of the academic club moderators, centering on pivotal variables including Idealized In-fluence, Inspirational Motivation, Intellectual Stimulation, and Individual Consideration. The study seeks to validate the transformational leadership style of club moderators by considering factors such as age, sex, club affiliation, and club status. Furthermore, it explores the significance of differences in the assessments provided by respondents based on the collated profiles. Through a thorough analysis of these elements, the research aims to offer valuable insights into the dynamics of leadership programs, the formulation of development plans for club membership, and the enhancement of student activities within academic clubs. By shedding light on the varying degrees of transformative influence exerted by moderators on club members, this study endeavors to enrich the understanding of leadership dynamics and facilitate the cultivation of effective leadership strategies within the academic context.